Interspecific facilitation of micronutrient uptake between cluster-root-bearing trees and non-cluster rooted-shrubs in a Banksia woodland - Staudinger, Christiana; Renton, Michael; Leopold, Matthias; Wasaki, Jun; Veneklaas, Erik J.; de Britto Costa, Patrícia; Boitt, Gustavo; Lambers, Hans (Plant and soil, 2024)
Background and aims Belowground interspecific plant facilitation is supposed to play a key role in enabling species co-existence in hyperdiverse ecosystems in extremely nutrient-poor, semi-arid habitats, such as Banksia woodlands in southwestern-Australia. Manganese (Mn) is readily mobilised by Banksia cluster root activity in most soils and accumulates in mature leaves of native Australian plant species without significant remobilisation during leaf senescence. We hypothesised that neighbouring shrubs are facilitated in terms of Mn uptake depending on distance to surrounding cluster root-forming Banksia trees. Methods We mapped all Banksia trees and selected neighbouring shrubs within a study site in Western Australia. Soil samples were collected and analysed for physical properties and nutrient concentrations. To assesses the effect of Banksia tree proximity on leaf Mn concentrations [Mn] of non-cluster-rooted woody shrubs, samples of similarly aged leaves were taken. We used multiple linear models to test for factors affecting shrub leaf [Mn]. Results None of the assessed soil parameters showed a significant correlation with shrub leaf Mn concentrations. However, we observed a significant positive effect of very close Banksia trees (2 m) on leaf [Mn] in one of the understorey shrubs. We found additional effects of elevation and shrub size. Conclusions Leaf micronutrient concentrations of understorey shrubs were enhanced when growing within 2 m of tall Banksia trees. Our model predictions also indicate that belowground facilitation of Mn uptake was shrub size-dependent. We discuss this result in the light of plant water relations and shrub root system architecture.